Annual survey of English law - London School of Economics and Political Science. Department of Law. (London: London school of economics and political Science (University of London) Dept. of Law., 1931)
Each subdivision includes sections "Legislation", "Case law" and "Literature."
Reclassed from LAW <A&E Tre Annu>
Keywords: Law -- Great Britain; Law reports, digests, etc. -- Great Britain